Proliferation capability of natural killer cells upon cytokines stimulation correlated negatively with serum lactate dehydrogenase level in coronary artery disease patients - Guo, Xuemin; Xiao, Ting; Lin, Li; Gao, Qianqian; Lai, Bifa; Liu, Xianhui; Zhong, Zhixiong (Frontiers in Immunology, 2024)
Natural killer (NK) cells are proposed to participate in coronary artery disease (CAD) development.However, little is known about how CAD patients' NK cells respond to different stimulatory factors in terms of proliferation capability. Twenty-nine CAD patients' peripheral blood NK cells were isolated and individually treated with IL-2, IL-12, IL-15, IL-18, IL-21, cortisone acetate, hydrocortisone, or ascorbic acid for 36 hours, followed by cell cycle analysis using flow cytometry.The ratio of S and G2/M phase cell number to total cell number was defined as a proliferation index (PrI) and used for proliferative capability indication. The results showed that these eight factors resulted in different life cycle changes in the 29 NK cell samples. Remarkably, 28 out of 29 NK cell samples showed an obvious increase in PrI upon ascorbic acid treatment. The serum lactate dehydrogenase (LDH) level of the 29 CAD patients was measured. The results showed a negative correlation between serum LDH level and the CAD patients' NK cell PrI upon stimulation of interleukins, but not the non-interleukin stimulators. Consistently, a retrospective analysis of 46 CAD patients and 32 healthy donors showed that the circulating NK cell number negatively correlated with the serum LDH level in CAD patients. Unexpectedly, addition of LDH to NK cells significantly enhanced the production of IFN-γ, IL-10 and TNF-α, suggesting a strong regulatory role on NK cell's function. Altogether, ascorbic acid could promote the proliferation of the CAD patients' NK cells; LDH serum level may function as an indicator for NK cell proliferation capability and an immune-regulatory factor.